Composites for Life - Pedro Duarte Menezes; Tomás de Meireles Carneiro; António Torres Marques (U.Porto Journal of Engineering, 2021)
The usage of bio-fibres and recycled materials is a growing approach to address the ecological problems being faced today. Inspired by the guidelines defining the Waste for Life initiative, the present study reports new composite materials, based on the recycling of high-impact polystyrene, found, for instance in yogurt cups, and paper plastic laminates, deriving from disposable paper cups. Given their recycling incompatibility, paper plastic laminates are either dumped in landfills or incinerated after their first usage, threatening the environmental condition. Therefore, through the development of a new composite solution, the goal was to reduce this damaging environmental impact by providing a second life to both paper plastic laminates and high-impact polystyrene. Samples presented overall good mechanical properties, from which it is highlighted a Young’s Modulus of 1.75 GPa and a Tensile Strength of 21.2 MPa, encouraging the application of the present material to identified global obstacles.